Post-Treatment of Anaerobically Treated Medium-Age Landfill Leachate - Akkaya, Ebru; Demir, Ahmet; Karadag, Dogan; Varank, Gamze; Bilgili, M. Sinan; Ozkaya, Bestamin (WILEY, 2010)
This study focused on the removal of COD and NH4+ from medium-age leachate. Experiments were performed in a laboratory-scale upflow anaerobic sludge blanket (UASB), a membrane bioreactor (MBR), and using magnesium ammonium phosphate (MAP) precipitation, MBR and MAP were used for the post-treatment steps for anaerobically treated leachate to increase the removal of organics and ammonium. The UASB reactor removed nearly all biodegradable organics and supplied constant effluent COD for all concentration ranges of influent leachate. Ammonium removal efficiency in the UASB reactor was relatively low and the average value was similar to 7.9%. Integration of MBR to the effluent of UASB reactor increased the average COD removal efficiency from 51.8 to 65.6% and maximum removal efficiency increased to 74.3%. MAP precipitation was applied as a final step to decrease the ammonium concentration in the effluent of UASB+MBR reactors. The effect of pH and the molar ratio of MAP constituents on the removal of ammonium were evaluated. At optimal conditions (pH: 9.0 and Mg/NH4/PO4: 1/1.2/1.2), 96.6% of ammonium was removed and MAP provided additional COD and turbidity treatment. Consequently, the combined system of MBR and MAP precipitation could be used as an appropriate post treatment option for the anaerobically treated medium-age landfill leachate. (C) 2009 American Institute of Chemical Engineers Environ Prog, 29: 78-84, 2010
Keywords: ammonium; leachate; magnesium ammonium phosphate precipitation; membrane bioreactor; upflow anaerobic sludge blanket reactor; AMMONIUM PHOSPHATE PRECIPITATION; SUBMERGED MEMBRANE BIOREACTOR; HIGH-STRENGTH; CHEMICAL PRECIPITATION; STRUVITE PRECIPITATION; AEROBIC TREATMENT; NITROGEN REMOVAL; MUNICIPAL; DEGRADATION; SLUDGE; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology